2018
DOI: 10.4062/biomolther.2017.225
|View full text |Cite
|
Sign up to set email alerts
|

Fasiglifam (TAK-875), a G Protein-Coupled Receptor 40 (GPR40) Agonist, May Induce Hepatotoxicity through Reactive Oxygen Species Generation in a GPR40-Dependent Manner

Abstract: Fasiglifam (TAK-875) a G-protein coupled receptor 40 (GPR40) agonist, significantly improves hyperglycemia without hypoglycemia and weight gain, the major side effects of conventional anti-diabetics. Unfortunately, during multi-center Phase 3 clinical trials, unexpected liver toxicity resulted in premature termination of its development. Here, we investigated whether TAK-875 directly inflicts toxicity on hepatocytes and explored its underlying mechanism of toxicity. TAK-875 decreased viability of 2D and 3D cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Both GW9508 and TAK-875 effectively agonize Gpr40 but they also activate other G protein receptors. Kim et al showed that high doses of TAK-875 (50, 100, 250 and 500 µM) dose-responsively induce the death of HepG2 cells, 25 which was found to be associated with the induction of hepatic ROS generation. Philippe et al report that a high dose of GW9508 (100 µM) decreases the proliferation of osteoblast precursor cell line RAW264.7.…”
Section: Discussionmentioning
confidence: 99%
“…Both GW9508 and TAK-875 effectively agonize Gpr40 but they also activate other G protein receptors. Kim et al showed that high doses of TAK-875 (50, 100, 250 and 500 µM) dose-responsively induce the death of HepG2 cells, 25 which was found to be associated with the induction of hepatic ROS generation. Philippe et al report that a high dose of GW9508 (100 µM) decreases the proliferation of osteoblast precursor cell line RAW264.7.…”
Section: Discussionmentioning
confidence: 99%
“…While GPR40 agonists, palmitic acid, and oleic acid act through G q/11 -mediated mechanisms, the synthetic agonist TAK-875 can act as a β-arrestin2-biased agonist, engaging β-arrestin2-dependent signaling to induce the insulinotropic activity of GPR40 ( 13 ). The biased GPR40 activation has shown a promising potential as a therapeutic target to enhance insulin secretion in T2D ( 79 ), but phase III clinical trials with TAK-875 were recently terminated due to signs of liver toxicity in patients ( 81 ). Therefore, therapies based on GPR40 agonism provide an attractive alternative in the discovery of antidiabetic drugs, but further studies are needed to determine if potential side effects induced by this approach can be avoided.…”
Section: Gpcr Signaling Pathways In Metabolismmentioning
confidence: 99%
“…It is expressed in the insulin-secreting cells where its ligands augment the elevated plasma glucose-induced secretion of insulin [45]. In Phase III clinical trials, Takeda Pharmaceuticals' GPR40 agonist, fasiglifam (TAK-875) significantly improved hyperglycemia without hypoglycemia and weight gain but was discontinued because of unexpected liver toxicity [46]. More GPR40 modulators have been disclosed in WO/2004/041266 (Takeda Pharmaceutical Co., Ltd), WO/2007/033002 (Amgen, Inc.), and WO/2009/157418 (Daiichi Sankyo Co. Ltd), but in the present application Boehringer Ingelheim has improved on the compounds disclosed in its own application WO/2013/178575 in terms of potency, solubility and chemical stability at acidic pH.…”
Section: Wo/2018/086530mentioning
confidence: 99%